Determination the Relationship between Some genetic Aspects with the Capsule Formation for Pathogenic Klebsiella pneumoniae Serotypes K1 &K2 - Abd Al-Rhman, Rand M.; A. Al-Aubydi, Mouruj (Iraqi Journal of Science, 2023)
A total of 47 samples were collected from different clinical specimens (urine, wounds, burns, sputum, blood, stools) during the period from November 2013 toJanuary 2014, only 18 isolates (38.29%) were identified as Klebsiella pneumoniae ,11isolates (23.4%) as E. coli , 9 isolates (19.1%) as S. aureus, 3isolates (6.3%) as Psedomonase spp., 2 isolates (4.2 %) as K. terrigena and 4 isolates (8.5%) as K. oxytoca. The results were shown the elevation of K. pneumoniae percentage among the bacterial isolates depending on cultural, microscopically, biochemically characteristics and confirmed by using the API 20E and VITEK 2 system . Also K. pneumoniae isolates were more frequently in sputum samples then burns, stools , urine, wounds ,and blood in different percentages (33.3%, 16.6%, 16.6%, 11.1%,11.1%, 11.1%) respectively. The in vitro sensitivity tests of K. pneumoniae isolates against (19) antimicrobial agents were determined through disc-diffusion method. It was found that all isolates were 100% resistant to (Ampicillin /Cloxacillin, Amoxicillin, Carbencillin, Oxacillin, Penicillin G and Ceftazipime, whereas they indicated variable resistance to the other antibiotics used. While Amikacin , Gentamicin and Imipenem revealed that were the most effective drugs used in the present study. Moreover K. pneumoniae isolated from sputum, urine and blood samples are more resistant to antimicrobial agents at percentages (78.9%), the most resistance isolates, 6 isolates were selected .The molecular detecting of some capsular polysaccharide genes (cps) were investigated by using PCR specific primers. Genotyping of 6 selected K. pneumoniae isolates were indicated by using K1,K2 specific PCR primers. The results were shown ,that there is no isolate belong to K1 serotype, while 4 isolates (66.6%) are belonged to K2 serotype, and 2isolates (33.3%) showed negative result for both K1/K2.